THE COGNITIVE SCREENING IN CHILDREN UNDER FIVE YEARS OLD IN DEVELOPING COUNTRIES: A SYSTEMATIC LITERATURE REVIEW - Siti Aisah; Kemal Nazarudin Siregar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Stunting or being too short affects one-third of children under five years old in developing countries. Stunting has long-term effects on cognitive development, school performance and economic productivity in adulthood. Early detection of cognitive impairment caused by stunting offers rapid strategies for reducing stunting by examine the consequence on cognitive development. Reliable assessment tools are necessary to properly track cognitive development caused by stunting. This studyidentifies that the use of appropriate cognitive assessment tools assists in early detection of the impact of stunting in children under five years old in developing countries. Methods: Systematic literature review using PRISMA-P guidelines were applied for this study. Studies were identified from 4 electronic sources (Scopus, Science Direct, EBSCO and Google Scholar) from 2015 to 2018 using relevant keywords. All studies were conducted on children under five years old in developing countries. The used studies for this review are limited to full-text in English and Bahasa Indonesia. Studies conducted from 19 April to 11 May 2018. Results: From 492 studies that have been extracted, there are 10 studies reported the cognitive impairment assessment tools for under five years old children used in developing countries. The satisfying assessment tools in eligibility criteria are Bayley Scales of Infant Development (BSID III), the Indonesian child development pre-screening questionnaire (Kuesioner Pra-Skrining Perkembangan/KPSP ) and Denver Developmental Screening Test (DDST II). They appear promising to be used in identifying and monitoring cognitive development of children in developing countries. Conclusions: In the context of stunting in children under five years old, rapid assessment of cognitive ability is feasible for routine clinical use. The BSID III, KPSP and DDST II are the most common used in developing countries and they have moderately good accuracy to detect the cognitive impairment.